Morphological and genetic confirmation of Jassa slatteryi (Crustacea: Amphipoda) in a harbour of Argentina - Rumbold, Carlos Enrique (2015)
Jassa slatteryi is reported for the first time in Mar del Plata harbour, Argentina. A morphological comparison with the original description and a genetic analysis are made to corroborate the identification of specimens. The report of range expansion along the South-western Atlantic coast is discussed.